Assessing the suitability of airport ground handling agents. (March 2020) - Skorupski, Jacek; Grabarek, Iwona; Kwasiborska, Anna; Czyżo, Sebastian
Abstract: Aircraft ground handling is an essential part of an air operation and determines its punctuality and safety. Ground support equipment vehicles (GSE) are used in most of the handling tasks. This puts certain requirements on the candidates for ground handling agents, especially on their psychophysical features. This study aimed at determining a professional profile of the candidate, defining expectations and requirements for the future employee and developing a quantitative method of assessing suitability for work as a GSE operator. Since some features characterizing the employee are not measurable, and the relations between features are imprecise and often subjective, fuzzy models based on linguistic variables were used to build the assessment method. A computer implementation of the fuzzy inference system was used for the assessment of exemplary candidates for the position of fuel tanker operator. The obtained results show that the applied approach makes it possible to easily compare the candidates' suitability for work at this position. The simulation experiments also showed that the method allows for the creation of individualized training programs based on partial assessments of individual traits of candidates. Highlights: Airport ground support equipment (GSE) operators must be carefully selected. A method for initial quantitative assessment of the GSE operator was developed. Hierarchical fuzzy reasoning system was used to build and implement the method. Candidates for the position of a tanker truck operator at the airport were compared. Traits whose training can contribute to improving the assessment were identified.